Islamic Education Policy in the Framework of Integration-Interconnection: Bridging Religious Knowledge and Scientific Disciplines in Islamic Education - Moh. Affan; Madlubur Rhisky; Abd. Muis (Lembaga Penerbitan, Penelitian dan Pengabdian kepada Masyarakat, Institut Badri Mashduqi, 2026)
This study examines the integration of Maqāṣid al-Sharīʿah into educational technology within the context of contemporary Islamic education. The rapid development of digital technology has transformed educational systems globally, creating both opportunities and ethical challenges related to human values, social responsibility, and educational sustainability. This research aims to analyze how the principles of Maqāṣid al-Sharīʿah can function as a normative framework for the development and implementation of educational technology, particularly in fostering ethical, adaptive, inclusive, and sustainable digital pedagogy. The study employs a qualitative literature review approach by analyzing scholarly sources, including journal articles, academic books, conference proceedings, and research reports related to educational technology, Islamic education, digital pedagogy, and Islamic ethical philosophy. The findings indicate that educational technology should not merely prioritize efficiency and technological innovation but must also protect essential human values such as intellectual integrity, moral responsibility, social justice, and human welfare. The study further reveals that Maqāṣid al-Sharīʿah provides a comprehensive ethical foundation for addressing issues such as digital dependency, algorithmic bias, educational inequality, and the dehumanization of learning environments. In addition, digital pedagogy based on Maqāṣid al-Sharīʿah demonstrates significant potential in promoting adaptive, inclusive, and sustainable Islamic education while preserving spiritual and humanitarian values in the digital era. This study contributes theoretically to the discourse of Islamic educational reform by proposing an integrative relationship between educational technology and Maqāṣid al-Sharīʿah as a framework for developing value-oriented digital education.